The Orthographic Norm in the Editions of Nušić's "Hajduci" and the Needs of Modern Teaching - Goran N. Zeljić (University of Belgrade, Teacher Education Faculty, 2021)
Using the example of "Hajduci" by Branislav Nušić, as school extensive reading for the fifth grade of primary school, this paper analyzes the compliance of ten selected editions of this work with the orthographic norm that was current at the time when these editions were published. Ten editions of this work were selected, starting from the first edition (1933/34), to the most recent one (2018), aiming to cover both periods of Serbian orthographic norm - the first, Belić's period, with the editions from 1923, 1930, 1934, 1950, and the second period, of Matica Srpska orthographic norm, with the editions from 1960 (together with Matica hrvatska), and in 1993 and 2010 whose authors are M. Pešikan, М. Pižurica and J. Jerković. In order to emphasize the importance of this analysis for teaching practice, it also includes the textbooks (readers) containing the excerpts from the novel "Hajduci". Bearing in mind that the students' language competencies in the field of grammar and orthographic norms are also developed by reading the works included in the reading lists, such as Nušić's "Hajduci", the aim of this paper is to determine to what extent, and according to which orthographic rules, the publishers of the later editions of this novel harmonised it with the current ortographic norm.